Exploring the impact of TV advertising and social media influencers in culinary marketing - Chelsy Angelia Timothy; Shinta Shinta; Fransiska Fransiska; Fifi Angelita (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This quantitative research aims to analyze and determine the impact of TV advertising and social media influencer endorsements on buying interest in the culinary field.Method — This research is quantitative in nature, focusing on individuals in Indonesia who utilize and watch digital TV. The research population includes those who meet the specified criteria. A total of 113 respondents participated, and primary data was collected through online questionnaires. The data analysis employed regression techniques.Result — As a result of this study, both social media influencers and TV advertising have been found to positively and significantly influence buying interest.Novelty — This research is pioneering in examination of digital TV advertising within the culinary field, and it extends its scope by investigating the widely used advertising medium of social media influencers.